2003
DOI: 10.1038/oby.2003.209
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Leptin on Nitric Oxide Production Is Impaired in Dietary‐Induced Obesity

Abstract: BELTOWSKI, JERZY, GRAŻ YNA WÓ JCICKA, AND ANNA JAMROZ. Stimulatory effect of leptin of nitric oxide production is impaired in dietary-induced obesity. Obes Res. 2003;11:1571-1580. Objective: We investigated the effect of leptin on nitric oxide production in lean and rats made obese by a highcalorie diet. Research Methods and Procedures:The animals were placed in metabolic cages, and urine was collected in 2-hour periods after leptin (1 mg/kg intraperintoneally) or vehicle administration. Blood was obtained 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
0
15
1
Order By: Relevance
“…In the remaining animals obesity was induced by feeding them highcalorie "cafeteria diet" for either 1 or 3 months. High-calorie diet consisted of standard chow combined 1:1 (wt/wt) with a liquid diet containing equal amounts (grams) of sucrose, glucose, whole milk powder and soybean powder suspended in tap water (Bełtowski et al, 2003). The composition of this diet was similar to standard chow (66% carbohydrates, 20% protein, and 14% fat).…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remaining animals obesity was induced by feeding them highcalorie "cafeteria diet" for either 1 or 3 months. High-calorie diet consisted of standard chow combined 1:1 (wt/wt) with a liquid diet containing equal amounts (grams) of sucrose, glucose, whole milk powder and soybean powder suspended in tap water (Bełtowski et al, 2003). The composition of this diet was similar to standard chow (66% carbohydrates, 20% protein, and 14% fat).…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Second, leptin-induced vasodilation in human coronary (Matsuda et al, 2003) and forearm (Nakagawa et al, 2002) circulation was not affected by NOS blockade. Third, in experimentally induced obesity leptin does not elevate blood pressure despite impaired effect on NO production, suggesting that other hypotensive mechanisms compensate for NO deficiency (Bełtowski et al, 2003). The mechanism of NOindependent vasodilatory effect of leptin is, however, unclear.…”
Section: Introductionmentioning
confidence: 97%
“…To explain this, recent studies have demonstrated the impairment of leptin's metabolic effects and leptin-induced NO production, i.e. "leptin resistance", in obesity (Beltowski et al 2003;Rahmouni et al 2005) and human hypertension (Tsuda and Nishio 2004). Leptin resistance may be caused by inflammatory mechanisms, as CRP impairs intracellular leptin signaling (Correia et al 2002;Chen et al 2006).…”
Section: Adipokinesmentioning
confidence: 99%
“…Second, although the primary effect of leptin on blood pressure may be the central stimulation of sympathetic nerve activity ( 24 ), other studies have suggested that leptin may have another, contradictory effect on blood pressure-i.e. , a vasodilative action that may or may not be related to a release of nitric oxide from the vascular endothelium ( 25 -27 ), and the stimulatory effect of leptin on nitric oxide was possibly modified by the degree of obesity ( 28 ).…”
Section: Introductionmentioning
confidence: 99%